Intravitreal Ranibizumab Injection as A Treatment for Diabetic Macular Edema - Defayudina Dafilianty Rosataria; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2020)
Introduction: In general, diabetic retinopathy is classified into early stage, namely non proliferative diabetic retinopathy (NPDR), and advanced stage, proliferative diabetic retinopathy (PDR). Diabetic macular edema is the most common cause of visual impairment in cases of early stage or NPDR. Purpose: To describe Diabetic Macular Edema (DME) with intravitreal injection of anti-VEGF as a treatment. Case presentation: 43 old female, came with chief complaint of blurred vision on her right eye since six months ago. Blurring is felt slowly. Patient has a history of uncontrolled diabetes since 10 years and a history of hypercholesterolemia since 1 year ago. visual acuity of the right eye is 4/60. On posterior segment examination, neovascularization of the papilla was found. Decreased foveal reflex (+), hard exudates (+) within 500 µm from the central macula. Microaneurism (+), dot hemorrhage (+), blot (+) in 4 quadrants, hard exudates (+) in 2 quadrants in her right eye. The patient was planned for intravitreal injection of anti-VEGF on her right eye. Conclusion: Intravitreal injection of anti-VEGF can improve visual acuity and reduce exudate and hemorrhage in retina from ophthalmoscope and fundus photography examination. In addition, the investigation with OCT was found to improve with reduced macular thickness.